THE PROMOTION IN DEMOCRATIC POLITICAL PARTICIPATION OF UNIVERSITY STUDENTS IN PHITSANULOK PROVINCE - Kettong, Dawnapa; Thong-in, Termsak; Suyaporm, Surapol (Journal of MCU Phetchaburi Review, 2023)
The objectives of this research were: 1) to study the general condition and problems and obstacles in the development of the promotion of democratic political participation among university students in Phitsanulok Province; Democracy of university students in Phitsanulok Province and 3) to present the development of promotion of democratic political participation among university students in Phitsanulok province, a qualitative research methodology. The key informants were 20 figures or persons, a specific group discussion of 12 figures or persons by descriptive data analysis. and quantitative research The sample group consisted of 391 people. The results showed that General conditions and problems and obstacles in the development of the promotion of democratic political participation among university students in Phitsanulok Province are: general conditions: elections, participation in political campaigning activities; election observation voting keep track of vote counting As for problems and obstacles: conservative groups, friends, family, social capital and lifestyle. The overall quantitative level was at a high level ( = 4.12) 2.Promoting the development and promotion of democratic political participation among university students in Phitsanulok Province: 1) Student Affairs Organizing activities for students to participate in the knowledge of democracy Organizing courses on civic duty and opening up space for constructive political participation 2) participation aspect Universities should emphasize students’ participation in politics. The course should build good citizenship. political commentary and creating a sense of citizenship rather than citizenship; and 3) knowledge. Access to information via online media via website, through music, through rap, case studies, popular trends, curricula development activities and student development activities The overall quantitative level is at a high level ( = 4.12) 3. Development of promotion of democratic political participation among university students in Phitsanulok Province: 1) Direct participation consisted of following news; suffrage starting to discuss political issues, campaigning, and proposing ideas policy proposal to politicians political movement Political membership and setting rules 2) Indirect participation consists of expressing opinions on political phenomena. Commenting on the clubhouse, Facebook and social media exchanging political issues a study of the policies of candidates and political parties and participation in political activities; should promote the views of the university administration Opinions on the regulation of the work of representatives or senators should be encouraged. Government agencies’ opinions on public policy issues should be encouraged. Opinions on participation in policy formation should be encouraged. and should promote opinions on the future development direction of the country in terms of economy society, education and occupation; event civil democratic process Community Democracy and public consciousness The overall quantitative level was at a high level ( = 3.93)